2020
DOI: 10.1108/intr-05-2019-0217
|View full text |Cite
|
Sign up to set email alerts
|

Design quality in building behavioral intention through affective and cognitive involvement for e-learning on smartphones

Abstract: PurposeThis study examines the effect of design quality (i.e. appearance, navigation, information and interactivity) on cognitive and affective involvement leading to continued intention to use the online learning application.Design/methodology/approachWe assume that design quality potentially contributes to enhance the individual's invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 123 publications
(302 reference statements)
1
34
0
Order By: Relevance
“…Alshehri et al [52] distinguished the different design features to assess online learning systems' usability as interactivity, visual design, navigation design, and learnability. This has been identified that the effect of design quality (i.e., appearance, navigation, information, and interactivity) on cognitive and affective involvement forces the user to use online learning application continuously [9]. In this way, a good quality site includes all the factors utilized to design and influence clients' inner condition.…”
Section: Design Artifatsmentioning
confidence: 99%
See 4 more Smart Citations
“…Alshehri et al [52] distinguished the different design features to assess online learning systems' usability as interactivity, visual design, navigation design, and learnability. This has been identified that the effect of design quality (i.e., appearance, navigation, information, and interactivity) on cognitive and affective involvement forces the user to use online learning application continuously [9]. In this way, a good quality site includes all the factors utilized to design and influence clients' inner condition.…”
Section: Design Artifatsmentioning
confidence: 99%
“…Content may change prior to final publication. ing positive perspectives towards the framework interface, which, eventually, prompts increased involvement [9], [53].…”
Section: Design Artifatsmentioning
confidence: 99%
See 3 more Smart Citations